How the Kuroshio Current Delivers Nutrients to Sunlit Layers on the Continental Shelves With Aid of Near‐Inertial Waves and Turbulence. Issue 12 (20th June 2019) - Nagai, Takeyoshi; Durán, Gloria Silvana; Otero, Diego André; Mori, Yasutaka; Yoshie, Naoki; Ohgi, Kazuki; Hasegawa, Daisuke; Nishina, Ayako; Kobari, Toru
Abstract: The Kuroshio Current carries a large amount of nutrients in dark subsurface layer along the southern coast of Japan. However, due to lack of sufficient multidisciplinary high‐resolution observations, it has been unclear whether and how the subsurface nutrients are injected to sunlit layers on the continental shelf. In this study, using a state‐of‐the‐art tow‐yo microstructure profiler and nitrate measurements, we show that the Kuroshio flowing on the shelfbreak induces very strong turbulent dissipation rate ∼O(10 −7 W·kg −1 ) and diffusivity ∼O(10 −3  m 2 ·s −1 ) over an across frontal scale of 20–30 km. This strong turbulence could provide a diffusive nitrate flux to euphotic zone of >O(1 mmol N·m −2 ·day −1 ). As the Kuroshio steadily runs on the continental shelves along the path, the nutrient injection found in this study is a very important supply for biological production on the continental margin along the southern coast of Japan. Key Points: Very strong turbulence is observed in the Kuroshio Current near shelfbreak over 30 km in the across frontal direction Turbulence is caused by banded internal wave shear amplified between the Kuroshio Current and the continental slope Turbulent mixing causes a large diapycnal diffusive nitrate flux to the euphotic zone over 30 km